Pengaruh CR, DER, dan TATO terhadap ROA Pada Perusahaan Manufaktur Subsektor Barang Konsumsi Yang Terdaftar di BEI - Daniel Suryadi Cornelius Lumban Tobing; Zulfa Khairina Batubara (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to examine the influence of CR, DER, and TATO variables on ROA in consumer goods subsector manufacturing companies listed on the IDX. With a sample of 11 companies, 4 years with a total of 44 observations, quantitative research methods and using multiple linear regression. The results of the simultaneous F test of CR, DER, and TATO variables have a significant effect on ROA obtained F count value > F table (3.211 > 2.84). The results of the partial t test of the CR variable have no effect on ROA because the t count value < t table (0.120 < 2.02108) and a significance of 0.905 > 0.05. The DER variable has no effect and is not significant on ROA t count value < t table (1.955 < 2.02108) and a significance of 0.058 > 0.05. The TATO variable has a significant effect on ROA with a calculated t value > t table (2.130 > 2.02108) and a significance of 0.039 < 0.05. The R2 test, Adjusted R Square value of 0.134 means that 13.4% of the variation or change in Return On Assets is explained by the CR, DER, and TATO variables, while 86.6% is influenced by other variables outside the study.